Interpersonal conflict and physicians’ entrepreneurial intention: Education and motivation as mediating roles - Sulaksono, Andri; Bungin, Burhan; Dewi, Liliana (Journal of Asian Scientific Research, 2025)
The study examines how interpersonal conflict (IC) influences physicians' entrepreneurial intention (EI), with entrepreneurial education (EE) and learning motivation (LM) serving as mediators. A survey of 150 Indonesian physicians was analyzed using PLS-SEM and FIMIX-PLS. The measurement model demonstrated acceptable fit indices, with SRMR = 0.083 and GoF = 0.365. Structural results indicate that EE (β = –0.461, p < 0.01) and LM (β = –0.330, p < 0.05) significantly decrease EI, whereas IC shows no significant direct or indirect effects; the IC–EI path is marginally significant p = 0.052. The mediation analysis confirms that EE and LM do not mediate the relationship between IC and EI. The model explains 57% of the variance in EI, although its predictive relevance is weak. These findings are robust, and the marginal significance of the IC–EI path (p = 0.052) is duly reported. FIMIX-PLS identifies three distinct physician segments: (i) cautious physicians, where both EE and LM reduce EI; (ii) motivation-oriented physicians, where LM increases EI despite EE’s negative effect; and (iii) education-oriented physicians, where EE increases EI but LM suppresses it. The results suggest that physicians’ entrepreneurial orientation is heterogeneous and influenced by paradoxical effects of education and motivation. This study extends EI models to the medical field, challenges the assumption of a positive role of education, and provides practical insights for designing targeted entrepreneurship programs and health policies in Southeast Asia, particularly Indonesia.